Taper equations adjusted for Corimbya citriodora Hill & Johnson using data generated by the relative height method. - Vieira Terra, David Lucas Camargo (2023)
In this study, the objective was to evaluate the fit of equations to describe the profile of the Corymbia citriodora stem using cubing data collected directly along the stem (real cubing) and indirectly by middle of the relative height method (hr cubing). For this, the shaft diameters were obtained in the positions: 0.2 m, 0.4 m, 0.7 m, 1.3 m, 2.70 m, and successively, every 2 m up to a diameter around 3 cm with shell. In the evaluation of the description of the shaft profile with the taper equations generated with data from the real and hr cubages, also of the volume by applying the Huber formula, the statistical criteria were adopted: mean residue, Bias, linear correlation, standard deviation of the residues, accuracy obtained by the chi-square test and the square root of the residue, in addition to analysis of the distribution of residues. Such criteria were obtained in a cross-validation using two cubing databases obtained by alternating the measurement positions of the shaft diameter. It was concluded that there is evidence of obtaining very close levels of accuracy in the use of taper equations generated from the data of real cubing and hr cubing, both in the description of the C. citriodora bole profile and in the quantification of its volume. Keywords: Tapering, Forest Measurement, multi-timber products.